Thrombolysis and Mechanical Thrombectomy as Leading Treatments for Acute Ischemic Stroke - Karolina Filipska; Adam Wiśniewski; Robert Ślusarz (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Brain vascular diseases, especially strokes, are still a very serious public health and medicine problem. The world is still facing an epidemic of stroke. With the impact load increasing all over the world, there is a continuing need to understand the characteristics of this disease and its impact in different countries. Despite significant improvements in primary prevention and treatment efficacy over the past decades, stroke is still a debilitating disease. Early treatment is the key to successful recovery of patients with ischemic stroke. The aim of the study is to show the most effective methods of treating patients in the acute phase of ischemic stroke. (JNNN 2019;8(4):177–181)